2022
DOI: 10.3390/jcm11113228
|View full text |Cite
|
Sign up to set email alerts
|

The Burden on Cohabitants of Patients with Chronic Spontaneous Urticaria: A Cross-Sectional Study

Abstract: Chronic Spontaneous Urticaria (CSU) has been associated with patients’ poor quality of life. Despite being a chronic disease that could alter the quality of life of the people who live with patients, the potential burden on their cohabitants has not been studied to date. The aim of this study is to analyze the relationship between the patient’s quality of life, disease control, disease duration and family quality of life and the cohabitant’s mood disturbances, sexual dysfunction, type D personality and sleep q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Females tend to be more affected by urticaria than males, and the disease seems more common among adults than among children and the average prevalence for lifetime of CSU risk is 1.4%. Therefore, a better understanding of its highly heterogeneous pathogenesis, which affects intracellular signaling defects and autoimmune processes, is needed [ 16 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Females tend to be more affected by urticaria than males, and the disease seems more common among adults than among children and the average prevalence for lifetime of CSU risk is 1.4%. Therefore, a better understanding of its highly heterogeneous pathogenesis, which affects intracellular signaling defects and autoimmune processes, is needed [ 16 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have addressed the issue of the quality of life of cohabitants of patients suffering from chronic diseases, such as inflammatory bowel disease [ 24 ], psoriasis [ 11 ], chronic spontaneous urticaria [ 25 ], or hidradenitis suppurativa [ 12 ]. In this line, there are many factors that could be responsible for this negative impact.…”
Section: Discussionmentioning
confidence: 99%
“…Children typically present with lower rates of angioedema (19% vs 60%) and shorter disease duration (5 vs 12 months) compared with adults [ 8 ]; a more comprehensive review of CSU management in children is beyond the scope of this paper but is provided elsewhere [ 9 , 10 ]. Cross-sectional, observational studies have shown that patients suffer a wide-ranging disease duration of 1–10 years [ 1 , 11 14 ], with approximately 40% of patients enduring the disease for longer than 10 years [ 11 ]. Disease trajectory and characteristics impact CSU duration, with a relapsing/remitting disease course, co-existing angioedema, and systemic complaints associated with prolonged disease duration [ 15 , 16 ].…”
Section: Characteristics and Clinical Presentationmentioning
confidence: 99%